An assessment of the companion modelling approach in a context of negotiating water allocation strategies : the case of the Kat River Valley, Eastern Cape, South Africa - Gumede, Felicity Hlengiwe (Rhodes University, Faculty of Science, Department of Geography, 2008)
This Masters research took place in the Kat River Valley in the Eastern Cape, South Africa. The Kat River Valley is a semi-rural catchment that covers an area of approximately 1700kmÂ² and is characterized by a complicated history of dispossession and resettlement. Farming is the main activity that is practiced in the area. This includes the farming of citrus at a commercial scale, rangeland stock farming and small-scale vegetable farming. The economy of the catchment is enhanced mostly by commercial citrus farming, which consumes by far the largest amount of water in the river through irrigation. Water allocation is a burning issue among water users in the catchment and needs to be negotiated taking into consideration social, economic and environment impacts. The aim of this study is to describe, discuss and evaluate the Companion Modelling (ComMod) approach, which used a simulation model and a role-playing game related to the model in order to facilitate and develop negotiating skills as well as build capacity in decision-making amongst local stakeholders for water resource management in the Kat River Valley. The ComMod approach, developed by a group of Companion Modellers, is a community-based science approach that emerged in the 1990s. The ComMod approach is used in order to facilitate collective learning, negotiation and institutional innovation in dealing with resource management complexities faced by rural communities. Through ComMod, the model (KatAWARE) and its related role-playing game was developed by having the contact with local stakeholders. The information to feed the model and the role-playing game came from informal interviews, surveys, geographic information systems (GIS), workshops and focus groups. The use of workshops in the implementation of ComMod was a success. Results show that (1) new knowledge was acquired, which allowed stakeholders to have a broad understanding of a catchment system. (2) Awareness was created about complex systems and enabled stakeholders to see an individual action into to the broader system. (3) Strong interrelationships were fostered amongst different water users, which allowed stakeholders to share their view points. The ComMod process was however associated with a number of limitations, many of which resulted from the constraints that were imposed by the socio-economic background of the study area. Nevertheless, the outcome of the study shows that the ComMod process was useful in helping the Kat River Water Users Association (KRWUA) stakeholders develop negotiating skills regarding water allocation strategies for the development of the Catchment Management Plan.
Keywords: Water supply -- South Africa -- Kat River Valley -- Management; Water resources development -- South Africa -- Kat River Valley; Integrated water development -- South Africa -- Kat River Valley